The rebel - Metz, Melinda; Copyright Paperback Collection (Library of Congress) (New York Pocket Pulse, 2000)
Michael has finally found the one thing he always yearned for--family. When his brother Trevor arrives in Roswell, Michael will do anything to please him. But soon Trevor's loyalties come into question and Michael is caught in the cross fire
1
Keywords: High school students -- Fiction; Occult fiction; Science fiction; Young adult fiction